SOCIOLINGUISTIC PECULIARITIES OF ADDRESSING IN THE ENGLISH LANGUAGE - aBoboyozova Nilufar G’ayratovna; Samigova Xushnuda Botirovna (Лучшие интеллектуальные исследования, 2024)
Annotation: This academic article delves into the sociolinguistic nuances of addressing within the English language. Addressing, or the way individuals refer to one another, is a complex aspect of communication influenced by cultural, social, and contextual factors. The article explores various forms of address, including formal and informal modes, titles, and honorifics, and examines their implications in different social settings. By considering variations in addressing across regions, age groups, and social classes, the study sheds light on the dynamic nature of linguistic interactions in English-speaking communities. Through an extensive literature review and empirical examples, the article aims to contribute to a deeper understanding of the sociolinguistic dimensions of addressing in the English language.